2017
DOI: 10.1186/s12874-017-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Using evaluability assessment to assess local community development health programmes: a Scottish case-study

Abstract: BackgroundEvaluation of the potential effectiveness of a programme’s objectives (health or otherwise) is important in demonstrating how programmes work. However, evaluations are expensive and can focus on unrealistic outcomes not grounded in strong theory, especially where there is pressure to show effectiveness. The aim of this research was to demonstrate that the evaluability assessment (a cost-effective pre-evaluation tool that primarily gives quick, constructive feedback) can be used to help develop progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The utility of logic models has been a frequent topic of BMC Medical Research Methodology [ 8 , 11 , 17 , 18 ]. Addressing the aforementioned debate, Greenwood et al question whether logic models can represent the dynamics of complex interventions that adapt to context, stating that “no matter how sophisticated, a logic model alone is not sufficient, as complexity cannot be understood purely through qualitative description” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of logic models has been a frequent topic of BMC Medical Research Methodology [ 8 , 11 , 17 , 18 ]. Addressing the aforementioned debate, Greenwood et al question whether logic models can represent the dynamics of complex interventions that adapt to context, stating that “no matter how sophisticated, a logic model alone is not sufficient, as complexity cannot be understood purely through qualitative description” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…45 The themes identified in this study are consistent with other community development evaluation studies in Tasmania (Australia), North India and Scotland that identified effective partnerships and found that government funding led to successful outcomes for community food security initiatives. [46][47][48] Adams and Taylor (2019) found that collaboration was essential for effective local food systems and that an innovative, diverse response was required to address community food security. 46 The authors recommended that all levels of government should preference social procurement contracts that enhance local food systems.…”
Section: Discussionmentioning
confidence: 99%
“…47 Limited time; lack of participation; lack of support from the community, local organisations and government; and limited resources were reported as factors that reduced the effectiveness of community development programs. 47,48 To counter these issues, the study reported a need to increase resourcing and service provision to enable nutritious food access for at-risk population groups. 46 A possible reason why initiatives in our study did not possess desirable characteristics was due to bureaucracy within organisations, particularly at a government level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations